Τhe Political Economy of Green Transition: The Need for a Two-Pronged Approach to Address Climate Change and the Necessity of “Science Citizens” - Antonios Angelakis; Manolis Manioudis; Anthi Koskina (Economies)
Given the need to strengthen responses to the growing challenges posed by climate change, the purpose of this paper is to explore innovative approaches and interdisciplinary perspectives for tackling these issues, focusing on the role of the institutional framework, emerging technologies, and the necessity to also encourage the involvement of small-scale actors (such as citizens). The main approaches of this paper involve, first, the technological developments spurred by the necessity to effectively address climate change problems, emphasizing macro-level dimensions in terms of the political economy of green transition and the technological components of climate solutions. Parallel to that, it provides results and presents key elements of the legal context that promoted the sustainable transition, such as the establishment of a science-based policymaking process, the development of scientific data and tools, and efforts to encourage the participation of all relevant actors in sustainable economic development. Against this background, this paper puts forward the idea that a combined approach is required to address climate change issues, integrating top-down, e.g., macro-policy approaches with bottom-up strategies (with the latter allowing for a more dynamic participation of citizens and individuals), in order to complement current institutional, legal, policy, and technological measures. The result of the analysis is that this paper provides evidence for the introduction of guidelines strengthening macro-economic approaches in addition to the concept of a “science citizen” as a major component of new problem-focused solutions. The principal results and findings offer interpretations and insights while encouraging further discussion on transitioning to a sustainable science society. In this context, the analysis results elucidate that there is evidence for an increased policy emphasis on technology development (economy-based approaches) rather than on technology diffusion and assessment, and/or the integration of key small-scale actors, such as citizens. Thus, this paper provides evidence for the need to incorporate “science citizens” as a key parameter into the technology and innovation chain (e.g., data provision) and the public policy domain. Overall, this paper outlines a holistic analysis of the international economic, technological, institutional, legal, and policy environment regarding innovation, sustainability, and the climate crisis.